Sustainable Biocompatible Materials for 3D Printed Fracture Casts: A Comparative FEA Analysis of Mechanical Properties and Environmental Impact - Deshpande, Akash; Thokal, Gajanan; Thokal, Ashwini; Pawar, Suyash; Chandratre, Kailas (Science & Technology Asia, 2023)
This research explores the environmental and medical significance of employing diverse biocompatible materials in the development of fracture casts, offering sustainable alternatives to conventional materials. Traditional casts contribute to environmental challenges as non-recyclable medical waste. In contrast, casts made from biomaterials not only address this issue but also ensure non-toxic and safe compatibility with human tissues. The study utilizes 3D printing technology for efficient manufacturing, contributing to both innovation in medical technology and reduced environmental impact. Through a comparative evaluation of three distinct biomaterials, the research provides insights into their mechanical properties. The virtual design and analysis employed showcase a systematic approach, enhancing the credibility of the study. By looking at how traditional casts affect the environment, making sure they are compatible with human tissues, encouraging innovation in manufacturing, and doing a full analysis of the materials, this research has the potential to lead to more sustainable and patient-friendly ways to treat fractures.